Molecular cloning, structural analysis and functional expression of the proline-rich focal adhesion and microfilament-associated protein VASP. - Haffner, C (1995)
The vasodilator-stimulated phosphoprotein (VASP), a substrate for cAMP- and cGMP-dependent protein kinases in vitro and in intact cells, is associated with actin filaments, focal adhesions and dynamic membrane regions. VASP, cloned here from human HL-60 and canine MDCK cells, is organized into three distinct domains. A central proline-rich domain contains a GPPPPP motif as a single copy and as a 3-fold tandem repeat, as well as three conserved phosphorylation sites for cyclic nucleotide-dependent protein kinases. A C-terminal domain contains a repetitive mixed-charge cluster which is predicted to form an alpha-helix. The hydrodynamic properties of purified human VASP together with the calculated molecular mass of cloned VASP suggest that the native protein is a homotetramer with an elongated structure. VASP over-expressed in transiently transfected BHK21 cells was predominantly detected at stress fibres, at focal adhesions and in F-actin-containing cell surface protrusions, whereas truncated VASP lacking the C-terminal domain was no longer concentrated at focal adhesions. These data indicate that the C-terminal domain is required for anchoring VASP at focal adhesion sites, whereas the central domain is suggested to mediate VASP interaction with profilin. Our results provide evidence for the structural basis by which VASP, both a target of the cAMP and cGMP signal transduction pathways and a component of the actin-based cytoskeleton, including the cytoskeleton-membrane interface, may be able to exchange signals between these networks.